A quantitative reverse transcription-polymerase chain reaction for detection of Getah virus - Sam, Sing-Sin; Teoh, Boon-Teong; Chee, Cheah-Mun; Mohamed-Romai-Noor, Noor-Adila; Abd-Jamil, Juraina; Loong, Shih-Keng; Khor, Chee-Sieng; Tan, Kim-Kee; AbuBakar, Sazaly (Scientific reports, 2018)
Getah virus (GETV), a mosquito-borne alphavirus, is an emerging animal pathogen causing outbreaks among racehorses and pigs. Early detection of the GETV infection is essential for timely implementation of disease prevention and control interventions. Thus, a rapid and accurate nucleic acid detection method for GETV is highly needed. Here, two TaqMan minor groove binding (MGB) probe-based quantitative reverse transcription-polymerase chain reaction (qRT-PCR) assays were developed. The qRT-PCR primers and TaqMan MGB probe were designed based on the conserved region of nsP1 and nsP2 genes of 23 GETV genome sequences retrieved from GenBank. Only the qRT-PCR assay using nsP2-specific primers and probe detected all two Malaysia GETV strains (MM2021 and B254) without cross-reacting with other closely related arboviruses. The qRT-PCR assay detected as few as 10 copies of GETV RNA, but its detection limit at the 95% probability level was 63.25 GETV genome copies (probit analysis, P ≤ 0.05). Further validation of the qRT-PCR assay using 16 spiked simulated clinical specimens showed 100% for both sensitivity and specificity. In conclusion, the qRT-PCR assay developed in this study is useful for rapid, sensitive and specific detection and quantification of GETV.